2020
DOI: 10.1007/s11897-020-00470-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TGF—β Signaling in Cardiomyocyte Proliferation

Abstract: Purpose of review-The loss of contractile function after heart injury remains one the major healthcare issues of our time. One strategy to deal with this problem would be to increase the number of cardiomyocytes to enhance cardiac function. In the last couple of years, reactivation of cardiomyocyte proliferation has repeatedly demonstrated to aid in functional recovery after cardiac injury.Recent findings-The Tgf-β superfamily plays key roles during development of the heart and populating the embryonic heart w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…Other agents involved in the interactions included BMP, LRP1 (low density lipoprotein receptor) and TNFR. BMP is a member of the TGF-beta superfamily and, along with NOTCH signaling, regulates CM proliferation (D’Amato et al, 2016; Sorensen and van Berlo, 2020). LRP1 affects cardiomyocyte lipid uptake, while TNFR activation may be involved in apoptosis, and has been described as recruiting cardiac progenitor cells (Allukian et al, 2013) and stimulating OFT CMs.…”
Section: Resultsmentioning
confidence: 99%
“…Other agents involved in the interactions included BMP, LRP1 (low density lipoprotein receptor) and TNFR. BMP is a member of the TGF-beta superfamily and, along with NOTCH signaling, regulates CM proliferation (D’Amato et al, 2016; Sorensen and van Berlo, 2020). LRP1 affects cardiomyocyte lipid uptake, while TNFR activation may be involved in apoptosis, and has been described as recruiting cardiac progenitor cells (Allukian et al, 2013) and stimulating OFT CMs.…”
Section: Resultsmentioning
confidence: 99%
“…TGFβ1, TGFβ2, and TGFβ3, pleiotropic factors belonging to the transforming growth factor beta (TGFβ) superfamily, have emerged as crucial mediators of multiple cellular responses in the infarcted myocardium, including cardiac reparative, inflammatory, angiogenic, and fibrotic responses [reviewed by Frangogiannis (117), Hanna and Frangogiannis (118) and Sorensen and colleagues (119)]. The inhibition of TGFβ receptor 1 (TGFBR1) activity by SB-431542 was reported to reduce the number of proliferating cardiomyocytes in zebrafish embryos (120).…”
Section: Growth Factors and Cytokinesmentioning
confidence: 99%
“…In addition, the analysis indicated that some m 6 A differential lncRNAs were also enriched in 'insulin-like growth factor receptor' and 'response to angiotensin', which are participating in cardiac hypertrophy [36,44]. m 6 A differential lncRNAs enriched in myocardial regeneration-related pathways, such as 'TGF-beta signaling pathway' is well documented [62]. All the above indicates that m 6 A differential lncRNAs may play an important role in the heart normal or dysfunction development.…”
Section: Discussionmentioning
confidence: 99%